Meteorological drivers and mortality associated with O3 and PM2.5 air pollution episodes in the UK in 2006. (15th September 2019) - Fenech, Sara; Doherty, Ruth M.; Heaviside, Clare; Macintyre, Helen L.; O'Connor, Fiona M.; Vardoulakis, Sotiris; Neal, Lucy; Agnew, Paul
Abstract: In this study we examine the meteorological drivers resulting in concurrent high levels of ozone (O3 ) and particulate matter smaller than 2.5 μm in diameter (PM2.5 ) during two five-day air pollution episodes in 2006 (1st - 5th July and 18th – 22nd July) using an air quality model (AQUM) at 12 km horizontal resolution to simulate air pollutant concentrations. The resultant UK health burden associated with short-term exposure to simulated maximum daily 8-h O3 (MDA8 O3 ) and daily mean PM2.5 is estimated at the national and regional level. Both episodes were found to be driven by anticyclonic conditions with light easterly and south easterly winds and high temperatures that aided pollution build up in the UK. The estimated total mortality burden associated with short-term exposure to MDA8 O3 is similar during the chosen episodes with about 70 daily deaths brought forward (summed across the UK) during the first and second episode, respectively. The estimated health burden associated with short-term exposure to daily mean PM2.5 concentrations differs between the first and second episode resulting in about 43 and 36 daily deaths brought forward, respectively. The corresponding percentage of all-cause mortality due to short-term exposure to MDA8 O3 and daily mean PM2.5 during these two episodes and across the UK regions, ranges from 3.4% to 5.2% and from 1.6% to 3.9%, respectively. The attributable percentage of all-cause mortality differs between the regions depending on the pollution levels in each episode, but the overall estimated health burdens are highest in regions with higher population totals. We estimate that during these episodes the short-term exposure to MDA8 O3 and daily mean PM2.5 is between 36-38% and 39–56% higher, respectively, than if the pollution levels represented typical seasonal-mean concentrations. This highlights the potential of air pollution episodes to have substantial short-term impacts on public health. Highlights: Both air pollution episodes are driven by anticyclonic conditions, light E/SE winds and high temperatures. The estimated mortality burden associated with short-term exposure to MDA8 O3 is up to 70 daily deaths brought forward. The estimated mortality burden associated with short-term exposure to PM2.5 is up to 45 daily deaths brought forward. The corresponding percentage of all-cause mortality due to short-term exposure to MDA8 O3 ranges from 3.4% to 5.2%. The corresponding percentage of all-cause mortality due to short-term exposure to daily mean PM2.5 ranges from 1.6% to 3.9% Short-term exposure to O3 and PM2.5 is between 36-56% higher during these episodes compared to summer air pollution levels